Fungi Isolation, Identification And Detection of Aflatoxins In Selected Cereals And Cereal Products - Akter, Tasmia; Shamsi, Shamim; Reza, Sompa; Nowar, Abira; Al Noman, Md Abdullah; Hassan, Mohammad Tariqul; Alim, Sharmin Rumi (Bioresearch Communications, 2024)
Background: The study aimed to detect toxigenic fungi and aflatoxin residues (B1, B2, G1, G2) in cereals and cereal products samples such as oats, rice, corn, corn flakes, wheat flour, and rice flour from local markets near Dhaka University, Bangladesh, due to the serious health risks posed by aflatoxins, produced by fungi Aspergillus flavus. Methods: A total of 130 samples were collected and the pooled 26 samples were analyzed. Associated fungi were isolated and cultured on a PDA medium and identified morphologically based on colony color, texture, diameter, and microscopic observation. Molecular identification was done by sequence analysis of the Internal Transcribed Spacer (ITS) region, confirming the presence of Aspergillus flavus. Aflatoxin residues were detected using High-Performance Liquid Chromatography (HPLC) with a fluorescence detector and the QuEChERS extraction method. Results: Out of 26 analyzed samples, 73.03% tested positive for aflatoxin residues (B1, B2, G1, G2), with an average concentration of 2.17 µg/kg. Two samples (wheat flour sample 3 and corn flakes sample 2) exceeded the Maximum Residue Limits (MRL) for aflatoxin B1 (2 µg/kg) and total aflatoxins (4 µg/kg) set by Commission Regulation (EC), representing 10.52% of the samples. Aspergillus spp., the primary producer of aflatoxins, was identified in 92.31% of the samples, alongside nine fungal genera and 19 fungal species. Conclusion: The study emphasizes the health risks of aflatoxin residues in foods like corn flakes and oats in Bangladesh, which may probably associated with serious conditions like cirrhosis and hepatocellular carcinoma, urging prompt action for food safety. Bioresearch Commu. 11(1): 1633-1642, 2025 (January)